Pediatric falls: literature review (Research, Society and Development, 2022)
This study, which is of a quanti-quali nature, sought as its general objective to carry out a bibliographic survey through a narrative literature review, cataloging and collation in turn information about traumatic falls in children (pediatric falls). For this scientific endeavor, a literature review was carried out here through the Google Scholar search engine, making use of Portuguese and English languages between the months of August and September 2020 through the following search expressions in the titles of the articles: “pediatric fall”, “pediatric fall”, “child fall” and “child fall”. It is noteworthy that 16 studies were found, only 3 in Portuguese and the other 13 in English. In summary, it is pointed out here that the research found in this study emphasize the extreme importance of a multidisciplinary work in the educational scope, in order to provide a collective act of prevention and safety for children.